2020
DOI: 10.1186/s40537-020-00379-6
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Intrusion Detection Systems Using a Feature Selection Method on the UNSW-NB15 Dataset

Abstract: Computer networks intrusion detection systems (IDSs) and intrusion prevention systems (IPSs) are critical aspects that contribute to the success of an organization. Over the past years, IDSs and IPSs using different approaches have been developed and implemented to ensure that computer networks within enterprises are secure, reliable and available. In this paper, we focus on IDSs that are built using machine learning (ML) techniques. IDSs based on ML methods are effective and accurate in detecting networks att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 289 publications
(134 citation statements)
references
References 37 publications
1
91
0
3
Order By: Relevance
“…ADFA-LD12 [19] IDS Limited to normal tracing. UNSW-NB15 [20] Tcpdump & netflow Uncorrelated synthetic netflow. CICIDS [21] Netflow Lack of triangulated features.…”
Section: Dataset Type Disadvantagementioning
confidence: 99%
See 1 more Smart Citation
“…ADFA-LD12 [19] IDS Limited to normal tracing. UNSW-NB15 [20] Tcpdump & netflow Uncorrelated synthetic netflow. CICIDS [21] Netflow Lack of triangulated features.…”
Section: Dataset Type Disadvantagementioning
confidence: 99%
“…It uses a set of limited records to approximate how the Machine Learning model performed during the training stage. It is a well-known Machine Learning method due to its simplicity and generally produces less biased estimation/prediction compared to other methods [6,20]. In short, cross-validation splits the data source into a training partition (80%) and the remaining partition (20%) is used as a testing set.…”
Section: Testing Ugransomementioning
confidence: 99%
“…Zhang et al [7] proposed an effective network traffic classification method, which used principal component analysis (PCA) to remove the irrelevant features and applied Gaussian Naive Bayes as the classifier. Kasongo et al [8] applied a filter-based feature reduction technique on the UNSW-NB15 data set using the XGBoost algorithm and then implemented several algorithms to classify the data. Results demonstrated that the feature selection method increased the test accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Although many have used feature selection algorithms such as Principal Component Analysis (PCA) [ 65 , 66 ], KNN [ 67 , 68 ], NB [ 69 , 70 ], LR [ 71 , 72 ], but recent works predominantly use RF [ 73 , 74 , 75 , 76 , 77 ] and XGBoost [ 78 , 79 , 80 , 81 , 82 ]. In particular, the authors in [ 83 ] provide a detailed analysis of RF-based feature selection.…”
Section: Related Workmentioning
confidence: 99%